An evaluation of an enzyme blend (natuzyme®) in diets for weanling pigs - Bergstrom, J.R.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two experiments were conducted to evaluate the effects of an enzyme blend (Natuzyme®) on nursery pig growth performance. In Exp. 1, a total of 210 pigs (initially 13.6 lb) were used in a 35-d experiment to evaluate the effect of increasing levels of Natuzyme® (0, 0.035, and 0.05%) on weanling pig performance. Natuzyme® was added to either a negative or positive control diet as a 2 × 3 factorial to form six dietary treatments. The negative control diet was a corn-soybean meal-based diet containing 12.5% soy hulls and no antibiotics. The positive control diet was a corn-soybean meal-based diet without soy hulls, and contained a feed-grade antibiotic (Neo-Terramycin with 140 g of neomycin and 140 g of oxytetracycline per ton). Pigs were blocked by weight and randomly allotted to treatment at weaning. Diets were fed in two phases from d 0 to 14 and d 14 to 35. For d 0 to 14, ADG and d 14 weight tended to improve (P<0.08) by feeding the positive control diets with a feed-grade antibiotic. There were also trends for improved (quadratic, P<0.09) ADG, ADFI, and d 14 weight with increasing Natuzyme®. There were no differences in performance from d 14 to 35. For the overall trial (d 0 to 35), ADG and d 35 weight tended to be improved (linear, P<0.09; and quadratic, P<0.07; respectively) for pigs fed increasing Natuzyme® and for pigs fed the positive control diets (P<0.07 and P<0.08, respectively) compared with pigs fed the negative control. In Exp. 2, a total of 180 pigs (initially 14.0 lb) were used in a 35-d experiment to further evaluate the effects of increasing Natuzyme® in diets with or without an antibiotic. Natuzyme® (0, 0.35, and 0.05%) was added to either a negative or positive control diet as a 2 × 3 factorial to form six dietary treatments. The negative control diet was a corn-soybean meal-based diet without a feed-grade antibiotic. The positive control diet was similar to that of the negative control diet, however, it contained a feed-grade antibiotic (Neo-Terramycin with 140 g of neomycin and 140 g of oxytetracycline per ton). Pigs were blocked by weight, and at weaning, randomly allotted to treatment with two dietary phases (d 0 to 14 and d 14 to 35). From d 0 to 14, pigs fed the positive control diet had improved (P<0.01) ADG, F/G, and d 14 weight compared to pigs fed the negative control. Average daily feed intake tended to be greater (P<0.06) for pigs fed the positive control diets. Also, pigs fed increasing Natuzyme® had improved ADG, F/G, and d 14 weight (linear, P<0.05). From d 14 to 35, pigs fed increasing Natuzyme® had poorer F/G (linear, P<0.05). Overall (d 0 to 35), ADG, ADFI, and d 35 weight were improved (P<0.01) for pigs fed the positive control compared to the negative control diet. When the observations for pigs fed the positive control diets (diets containing feed-grade antibiotic) in both experiments were combined, ADG from d 14 to 35 was improved (linear, P<0.06 and quadratic, P<0.02) with increasing Natuzyme®. Also, pigs fed increasing Natuzyme® had improved ADFI from d 14 to 35 (linear, P<0.03 and quadratic, P<0.01). Overall (d 0 to 35), ADG, ADFI, and d 35 weight were improved (linear and quadratic, P<0.05) by including Natuzyme® in the diet. In conclusion, pigs fed diets containing a feed-grade antibiotic had improved growth performance. The addition of Natuzyme® to corn-soybean meal-based diets also improved pig performance, particularly when included in diets containing a feed-grade antibiotic. However, in these studies, there did not appear to be a benefit to feeding more than 0.035% Natuzyme®.
Keywords: Swine; Enzymes; Antibiotics